Application of Bacteriophages to Limit Campylobacter in Poultry Production - Olson, Elena G.; Micciche, Andrew C.; Rothrock, Michael J.; Yang, Yichao; Ricke, Steven C. (Frontiers in Microbiology, 2022)
Campylobacter is a major foodborne pathogen with over a million U.S. cases a year and is typically acquired through the consumption of poultry products. The common occurrence of Campylobacter as a member of the poultry gastrointestinal tract microbial community remains a challenge for optimizing intervention strategies. Simultaneously, increasing demand for antibiotic-free products has led to the development of several alternative control measures both at the farm and in processing operations. Bacteriophages administered to reduce foodborne pathogens are one of the alternatives that have received renewed interest. Campylobacter phages have been isolated from both conventionally and organically raised poultry. Isolated and cultivated Campylobacter bacteriophages have been used as an intervention in live birds to target colonized Campylobacter in the gastrointestinal tract. Application of Campylobacter phages to poultry carcasses has also been explored as a strategy to reduce Campylobacter levels during poultry processing. This review will focus on the biology and ecology of Campylobacter bacteriophages in poultry production followed by discussion on current and potential applications as an intervention strategy to reduce Campylobacter occurrence in poultry production. .